Evaluation on efficiency of pyroligneous acid from palm kernel shell as antifungal and solid pineapple biomass as antibacterial and Plant Growth Promoter - Khairon Nisa Mahmud,; Maizatul Akmal Yahayu,; Siti Hajar Md. Sarip,; Nurul Husna Rizan,; Chai, Bing Min; Nurul Farhana Mustafa,; Sulaiman Ngadiran,; Salmiah Ujang,; Zainul Akmar Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Generation of huge volumes of lignocellulosic biomass from agricultural sector is of concern due to its direct effects on the depletion of overall environmental quality. Conversion of biomass into solid biofuel through pyrolysis reaction has become one of the solutions to manage the abundance of biomass. Pyroligneous acid (PA) produced from the condensation of smoke generated during biomass carbonization process has the potential to be applied in various applications based on the diverse active chemical compounds present. In this study, PA obtained from palm kernel shell (PKS) was evaluated for antifungal activity and solid pineapple biomass (PB) was evaluated for antibacterial and plant growth promoter activities. Higher antifungal activity was determined for crude PA from PKS (PA-PKS) and dichloromethane-extract (DPA-PKS) with 0% coverage area when evaluated using rubber wood blocks against mold and blue sapstain after for 4 weeks of observation. This antifungal activity can be attributed to the presence of phenols and its major derivatives as suggested from the GC-MS and FTIR analysis. Concentrated PA from PB displayed good antibacterial capabilities with almost similar growth inhibition for Escherichia coli (13±1 to 20±1 mm) and Corynebacterium agropyri (20±1 mm). PA-PB also showed good potential as PGP where the addition of 2% (v/v) of PA-PB into the fertilizer for okra plant resulted in highest number of leaves and fruits while 4% (v/v) PA-PB managed to give highest plant height, longest root, heaviest fruits and biggest leaf diameter. Thus, this